Maturogenesis of an Immature Dens Evaginatus Nonvital Premolar with an Apically Placed Bioceramic Material (EndoSequence Root Repair Material®): An Unexpected Finding - S. Nagarajan M. P. Sockalingam; Mohd Safwani Affan Alli Awang Talip; Ahmad Shuhud Irfani Zakaria (Case Reports in Dentistry)
Dens evaginatus is a dental developmental anomaly that arises due to the folding of the inner dental epithelium that leads to the formation of an additional cusp or tubercle on the occlusal surface of the affected tooth. This accessory tissue projection may carry with it a narrow and constricted pulp horn extension. Occasionally, the tubercle easily fractures, thus leading to microexposure of the pulp horn and eventual pulp necrosis. Often, the pulp necrosis occurs at a time the root development of the affected tooth is incomplete. Apexification with calcium hydroxide and mineral trioxide aggregates has been the mainstay of treatment options before root canal obturation in immature nonvital permanent teeth. Lately, regenerative endodontics (maturogenesis) is becoming one of the preferred treatment modalities to manage such teeth. The current case highlights the possibility of a bioceramic material (EndoSequence Root Repair Material, BC RRM-Fast Set Putty™, Brasseler, USA) which supposed to provide apical root closure (apexification) and could also induce continuation of root growth (maturogenesis).